2016
DOI: 10.1007/s13197-016-2267-z
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest treatment of antioxidant reduces lenticel browning and improves cosmetic appeal of mango (Mangifera indica L.) fruits without impairing quality

Abstract: The present study reports the usefulness of ascorbic acid for reducing lenticels browning (LB) in mango, which impairs the cosmetic appeal and thereby the export. Postharvest dip treatment of ascorbic acid at different concentrations (100, 150 and 200 ppm) was given to four varieties of mango (Indian-'Dashehari', 'Langra'; Exotic-'Sensation', 'Eldon'). After treatment, fruits were stored at ambient conditions (35 ± 4°C and 65 ± 5 % RH) for 10 days. At the end of storage period, observations were recorded on se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
1
26
1
Order By: Relevance
“…The phenolic compounds identified in banana peels in recent years were mainly dopamine, with dopaminerase oxidation being the main factor for banana browning [18]. Chlorogenic acid and epicatechin are the phenolic compounds with the highest contents in apple fruits [19], while the substrates in mango are mainly coffeic acid and ferulic acid [20]. Mishra et al [21] also showed that browning of eggplant was related to the content increased of polyphenols.…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic compounds identified in banana peels in recent years were mainly dopamine, with dopaminerase oxidation being the main factor for banana browning [18]. Chlorogenic acid and epicatechin are the phenolic compounds with the highest contents in apple fruits [19], while the substrates in mango are mainly coffeic acid and ferulic acid [20]. Mishra et al [21] also showed that browning of eggplant was related to the content increased of polyphenols.…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic compounds identified in banana peels in recent years were mainly dopamine, followed by chlorogenic acid and coumarin, with dopaminerase oxidation being the main factor for banana browning 19 . Chlorogenic acid and epicatechin are the phenolic compounds with the highest contents in apple fruits 20 , while the substrates in mango are mainly coffeic acid and ferulic acid 21 . In addition, some studies have shown that apple browning index (BI) is negatively correlated with hyperoside 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic compounds identified in banana peels in recent years were mainly dopamine, followed by chlorogenic acid and coumarin, with dopaminerase oxidation being the main factor for banana browning 36 . Chlorogenic acid and epicatechin are the phenolic compounds with the highest contents in apple fruits 37 , while in caffeic acid and ferulic acid are the main substrates in mangos 38 . Mishra et al .…”
Section: Discussionmentioning
confidence: 99%